Reading The Road with Paul Ricoeur and Julia Kristeva: The Human Body as a Sacred Connection - Arel, Stephanie (Text Matters: A Journal of Literature, Theory and Culture, 2014)
Cormac McCarthy’s novel The Road confronts readers with a question: what is there to live towards after apocalypse? McCarthy locates his protagonists in the aftermath of the world’s fiery destruction, dramatizing a relationship between a father and a son, who are, as McCarthy puts it, “carrying the fire.” This essay asserts that the body carrying the fire is a sacred, incandescent body that connects to and with the world and the other, unifying the human and the divine. This essay will consider the body as a sacred connection in The Road. Paul Ricoeur’s hermeneutics and Julia Kristeva’s psychoanalytic approach will help to explore what is sacred. In addition, their works elucidate the body as a present site of human connection and sacredness while calling attention to what is glaringly absent yet hauntingly present in McCarthy’s text: the mother. In the aftermath of destruction, primitive, sacred connections become available through the sensual body, highlighting what is at stake in the novel: the connection of body and spirit. The essay will attempt to show that McCarthy’s rejection of a redemptive framework, or hope in an otherworldly reality, shrouds spirit in physicality symbolized by the fire carried by the body. This spirit offers another kind of hope, one based on the body’s potential to feel and connect to the other. The thought and works of Ricoeur and Kristeva will broaden a reading of McCarthy’s novel, especially as a statement about the unification of body and spirit, contributing a multidimensional view of a contemporary problem regarding what sustains life after a cataclysmic event.